2006
DOI: 10.1111/j.1539-6975.2006.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Reinsurance Need Reinsurers?

Abstract: anonymous referee for very helpful comments. Errors are mine. AbstractThe reinsurance market is the secondary market for insurance risks. It has a very speci…c organization. Direct insurers rarely trade risks with each other. Rather, they cede part of their primary risks to specialized professional reinsurers who have no primary business. This paper o¤ers a model of equilibrium in reinsurance and capital markets in which professional reinsurers arise endogenously. Their role is to monitor primary insurers cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…An earlier remark by Lelyveld, Liedorp & Kampman (2009) noted that reinsurance companies enhance the overall underwriting capacity by freeing up the capital of primary insurers tied up to cover the risk. In consistence with the earlier opinions of the Group of Thirty (2006) and Plantin (2006), reinsurance offers services such as technical advice on underwriting and financial analysis, and thus, provides effective monitoring of ceding companies. The third hypothesis, H03, implies that there is no significant relationship between reinsurance and financial stability of insurance companies in Nigeria.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…An earlier remark by Lelyveld, Liedorp & Kampman (2009) noted that reinsurance companies enhance the overall underwriting capacity by freeing up the capital of primary insurers tied up to cover the risk. In consistence with the earlier opinions of the Group of Thirty (2006) and Plantin (2006), reinsurance offers services such as technical advice on underwriting and financial analysis, and thus, provides effective monitoring of ceding companies. The third hypothesis, H03, implies that there is no significant relationship between reinsurance and financial stability of insurance companies in Nigeria.…”
Section: Resultsmentioning
confidence: 89%
“…This theory, according to Iqbal, Rehman & Shahzad (2014), explicates the desires of a primary insurer to purchase reinsurance coverage against the risks it has assumed. Although, the core desire for demanding insurance or reinsurance coverage is risk sharing, since studies have shown that sharing risks optimally is not a singular reason for adopting reinsurance (Plantin, 2006). To this end, there is a need for risk diversification in a company's underwriting portfolio so as to curtail the chances of such companies being decimated by taking advantage of the expertise of reinsurance companies in being able to stabilize the shareholders' return (Doherty & Tinic, 1981).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, since the reinsurance sector collects a lot of information on insurance contracts, it can offer other services, such as consultancy, technical advice on underwriting and the financial analysis of risks and portfolios (Group of Thirty, 2006). Finally, as argued by Plantin (2006), reinsurers might provide effective monitoring of insurers. This enables insurers to raise capital more easily.…”
Section: Reinsurance Pros and Consmentioning
confidence: 99%
“…Its capitalization, all lines included, was estimated at the end of 2008 at $309 bn (Aon-Beneld, 2009). As underlined by Plantin (2006), the demand for reinsurance can be explained from two dierent points of view. Reinsurance can be used by insurance companies as a risk management tool (Borch, 1962;Blazenko, 1986;Lewis and Murdock, 1996;Froot, 2001;Froot and O'Connell, 2008) or from a capital structure perspective (Doherty and Tinic, 1981;Mayers and Smith, 1990;Garven and Tennant, 2003).…”
Section: Munichmentioning
confidence: 99%